2017
DOI: 10.1111/anu.12542
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of replacing fish meal with corn protein concentrate in Nile tilapiaOreochromis niloticusfingerlings commercial diet

Abstract: Four isocaloric-isonitrogenous diets containing 0, 50, 100 and 190 g/kg corn protein concentrate (CPC) as replacement for dietary fish meal were fed to Nile tilapia Oreochromis niloticus fingerlings for 8 weeks. Tilapia growth parameters were not significantly (p > .05) different in fish fed diets with 0, 50 and 100 g/kg CPC and found to be superior compared to those fed on 190 g/kg CPC. Fish dressing ratios and body composition were similar among all treatments. The electron microscope indicated that the stom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 39 publications
2
35
6
Order By: Relevance
“…Non‐lysine‐enhanced CPC (Empyreal ® 75; Cargill Corn Milling) with lysine content of about 11 g/kg (as is basis) had been evaluated as part of various protein blends for replacement of animal protein sources in the diets of Atlantic salmon Salmo salar (Burr, Wolters, Barrows, & Hardy, ) and Florida Pompano Trachinotus carolinus (Novriadi, Spangler, & Davis, ). High lysine CPC (Lysto ® ) has been reported for use as a protein blend in the diets of Florida Pompano (Cook, Zhou, Rhodes, & Davis, ) and as a direct replacement of dietary FM in the diets of Nile tilapia, Oreochromis niloticus (Khalifa, Belal, El‐Tarabily, Tariq, & Kassab, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Non‐lysine‐enhanced CPC (Empyreal ® 75; Cargill Corn Milling) with lysine content of about 11 g/kg (as is basis) had been evaluated as part of various protein blends for replacement of animal protein sources in the diets of Atlantic salmon Salmo salar (Burr, Wolters, Barrows, & Hardy, ) and Florida Pompano Trachinotus carolinus (Novriadi, Spangler, & Davis, ). High lysine CPC (Lysto ® ) has been reported for use as a protein blend in the diets of Florida Pompano (Cook, Zhou, Rhodes, & Davis, ) and as a direct replacement of dietary FM in the diets of Nile tilapia, Oreochromis niloticus (Khalifa, Belal, El‐Tarabily, Tariq, & Kassab, ).…”
Section: Introductionmentioning
confidence: 99%
“…The farming of red hybrid tilapia, Oreochromis sp., is very popular in Asia, thanks to its resemblance (coloration) to highly priced marine fish species such as sea bream Chrysophrys major and red snapper Lutjanus campechanus (Watanabe, Ernst, Olla, & Wicklund, ), which increases its market acceptance and value. Although it was reported that half of the dietary FM could be replaced in Nile tilapia diet with CPC (Khalifa et al, ), this has yet to be validated with red hybrid tilapia, especially in the context that CPC could have a negative effect on the skin colour, which play an important role in its market attractiveness. Furthermore, some aquafeed millers are reluctant to use corn‐based ingredients such as CGM and CPC due to the possibility of causing yellowing of fish fillets in fish species prized for their white flesh.…”
Section: Introductionmentioning
confidence: 99%
“…Khalifa et al . () reported that it is possible to replace up to 534 g kg −1 of fish meal in Oreochromis niloticus fingerlings using 100 g kg −1 of corn protein concentrate without any negative effect on fish growth and proximate body composition. In addition, Herath et al .…”
Section: Sources Of Proteinmentioning
confidence: 99%
“…Nowadays, plant protein and their by-products are a suitable strategy to increase the sustainability of aquaculture production by reducing feed costs as well as reducing the environmental adverse impact (Tacon & Metian, 2015). Several alternative plant protein sources in tilapia diets have been investigated in recent years due to the reduction in fish meal production and increasing its cost, such as cotton seed meal (El-Saidy & Gaber, 2004), okara meal (El-Saidy, 2011), fermented soybean meal (Hassaan, Soltan, & Abdel-Moez, 2015), soy protein concentrate (Ribeiro, Vidotti, Ferreira, & Gonçalves, 2016), Jatropha meal (Hassaan, Goda, & Kumar, 2017), corn protein concentrate (Khalifa, Belal, El-Tarabily, Tariq, & Kassab, 2018) and fermented sunflower meal (Hassaan et al, 2018), which were showed to be suitable as partial replacements for fish meal. However, total replacement of fish meal with plant proteins has generally resulted in decrease in fish growth performance and feed utilization.…”
Section: Introductionmentioning
confidence: 99%